FosA3 emerging in clinical carbapenemase-producing C. freundii - Mattioni Marchetti, Vittoria; Venturelli, Irene; Cassetti, Tiziana; Meschiari, Marianna; Migliavacca, Roberta; Bitar, Ibrahim (Frontiers in Cellular and Infection Microbiology, 2024)
Fosfomycin (FOS) is an effective antibiotic against multidrug-resistant Enterobacterales, but its effectiveness is reducing. Little is known on the current prevalence of FosA enzymes in low-risk pathogens, such as Citrobacter freundii. The aim of the study was the molecular characterization of a carbapenemase- and FosA-producing C. freundii collected in Italy. AK867, collected in 2023, showed an XDR profile, retaining susceptibility only to colistin. AK867 showed a FOS MIC >128 mg/L by ADM. Based on WGS, AK867 belonged to ST116 and owned a wide resistome, including fosA3, blaKPC-2, and blaVIM-1. fosA3 was carried by a conjugative pKPC-CAV1312 plasmid of 320,480 bp, on a novel composite transposon (12,907 bp). FosA3 transposon shared similarities with other fosA3-harboring pKPC-CAV1312 plasmids among Citrobacter spp. We report the first case of FosA3 production in clinical carbapenemase-producing C. freundii ST116. The incidence of FosA3 enzymes is increasing among Enterobacterales, affecting even low-virulence pathogens, as C. freundii.